Pretreatment with Lithospermic Acid Attenuates Oxidative Stress- induced Apoptosis in Bone Marrow-derived Mesenchymal Stem Cells via Anti-oxidation and Activation of PI3K/Akt Pathway - Li Wang-Yang; Zhou You-Liang; Li Tiao; Zeng Peng; Xu Wu-Ji; Lu Xiao-Long; Qi Xin-Yu; Xiong Hui (KeAi Communications Co., Ltd., 2019)
Objective: Despite the potential therapeutic approaches of bone marrow-derived mesenchymal stem cells (BMSCs) in orthopaedic, their applications are hampered by harsh oxidative stress conditions after transplantation. In this study, the anti- apoptotic and anti-oxidative properties of lithospermic acid (LSA) on BMSCs exposed to hydrogen peroxide (H2O2) were investigated. Methods: In the present study, we used H2O2 to induce oxidative injury on BMSCs. Reactive oxygen species (ROS) staining and superoxide dismutase (SOD) assay were performed. The expression levels of phosphorylated (p)-Akt, Bcl-2-associated X protein (Bax) and B-cell lymphoma 2 (Bcl-2) were measured by Western blotting. Results: LSA can significantly reduce H2O2-induced chromatin condensation and intracellular ROS levels, enhance the activity of SOD. Moreover, it can alleviate H2O2-induced apoptosis by up- regulating Bcl-2 and p-Akt, down-regulating Bax, which was blocked by the PI3K inhibitor, LY294002. Conclusions: Our results demonstrated that pretreatment with LSA could attenuate oxidative stress-induced apoptosis in BMSCs, which may be related with anti-oxidant properties and partly via modulating PI3K/Akt pathway, suggesting that pharmacologically manipulating BMSCs with LSA could be a promising drug to increase cell survival for BMSCs transplantation in musculoskeletal disorders of orthopaedic. Keywords: Oxidative stress, Lithospermic acid, Apoptosis, BMSCs, PI3K/Akt